EVALUASI RENCANA PEMBANGUNAN JALAN LINGKAR DI KOTA BANDA ACEH - R. Hendra, Yustina Niken (Jurnal HPJI, 2017)
Abstract The population of the City of Banda Aceh in the disaster prone areas, after the tsunami disaster, are likely to increase. The development of the area and the level of population mobility in the city, especially in areas prone to tsunami, created a variety of transportation problems in the city center and its surrounding areas. Therefore, in response to these conditions, the Government plans solutions to overcome the transportation problems. One of the solutions is to construct a ring road for the City of Banda Aceh. In this study, the implementation of two different development scenarios for the ring road construction was evaluated. For the Do Something in scenario 1, the construction of the ring road will be in 2031, while for the Do Something scenario 2, the ring road will be built in 2026. The average reduction of the V/C ratio given by the Do Something scenario 1 is 9.0%, which is less than that given by the Do Something scenario 2 (9.6%). It is concluded that the Do Something scenario 2 gives better results than the Do Something scenario 1. Keywords: engineering, traffic, geometric, scenario Abstrak Jumlah penduduk Kota Banda Aceh di daerah rawan bencana, pascabencana tsunami, cenderung bertambah. Pengembangan wilayah dan tingkat mobilitas penduduk di dalam kota, terutama di daerah rawan bencana tsunami, menyebabkan berbagai permasalahan transportasi yang berfokus di pusat kota dan sekitarnya. Oleh karena itu, menanggapi kondisi ini, pemerintah merencanakan solusi untuk mengatasi permasalahan transportasi tersebut. Salah satu solusi yang bisa diberikan adalah melakukan pembangunan jalan lingkar di Kota Banda Aceh. Dalam studi ini dilakukan penerapan dua skenario pembangunan jalan lingkar. Pada skenario Do Something 1 pembangunan jalan lingkar dilakukan pada tahun 2031 sedangkan dalam skenario Do Something 2 jalan lingkar dibangun pada tahun 2026. Besar rata-rata penurunan V/C ratio terhadap kondisi do nothing untuk penerapan skenario Do Something 1 adalah 9,0% sedangkan untuk penerapan skenario Do Something 2 adalah 9,6%. Penerapan skenario Do Something 2 memiliki hasil yang lebih baik dibandingkan dengan penerapan skenario Do Something 1. Kata-kata kunci: rekayasa, lalulintas, geometrik, skenario